Initiation of coconut cell suspension culture from shoot meristem derived embryogenic calli: A preliminary study - Bhavyashree, U.; Lakshmi Jayaraj, K.; Muralikrishna, K. S.; Sajini, K. K.; Rajesh, M. K.; Karun, Anitha (Journal of Phytology, 2016)
An attempt was made to establish highly competent embryogenic cell suspension culture in coconut, a species recalcitrant to in vitro culture. Embryogenic calli were initiated from shoot meristem explants of coconut. Y3 medium supplemented with 2.4-D (4.5 μM) and glutamine (34.2 μM) was found to be the best medium to initiate cell suspension. Growth evaluation was done by packed cell volume (PCV) and it was found that maximum growth volume of 9.9% was reached at 200 days of culture initiation. About 52% of viable cells were detected through fluorescent microscopy. Cell aggregation was noticed in Y3 medium supplemented with glutamine (34.2 μM), malt extract (100mg/l), biotin (40.9 μM) and kinetin (9.3 μM), but further progress could not be achieved. It was also observed that embryogenic calli were not of a friable type, but were associated with densely aggregated cells. Because of its hard nature, we were unsuccessful to obtain high quality cell suspension.